2020
DOI: 10.1080/21655979.2020.1739379
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid methyl ester analysis of Aspergillus fumigatus isolated from fruit pulps for biodiesel production using GC-MS spectrometry

Abstract: In this study, a total of six fungal samples were isolated from apple, strawberry and orange pulp. DNA sequence analysis was used as molecular identification method. ITS region was aligned in DNA sequence analysis, and an algorithm sequence similarity was done using BLAST (Basic Local Alignment Search Tool) program to identify these isolates. All the six isolates were identified as Aspergillus fumigates. The total lipid content was varied in the isolates which were ranged from 29.4 to 21.0 mg/100 ml. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 29 publications
0
6
1
Order By: Relevance
“…The finding here that medium-chain saturated capric acid was the dominant FAME in A. fumigatus and the second most abundant in Aspergillus sp. (BW4) contrasts the report from Asci et al (2020) who showed that the FAMEs profile of the six A. fumigatus strains studied were dominated by long-chain fatty acids and suitable for use as biodiesel.…”
Section: Discussioncontrasting
confidence: 61%
“…The finding here that medium-chain saturated capric acid was the dominant FAME in A. fumigatus and the second most abundant in Aspergillus sp. (BW4) contrasts the report from Asci et al (2020) who showed that the FAMEs profile of the six A. fumigatus strains studied were dominated by long-chain fatty acids and suitable for use as biodiesel.…”
Section: Discussioncontrasting
confidence: 61%
“…In the present study, 19 different types of FAMEs in SMB were reported for the first time (Table 2). The presence of long-chain fatty acids of FAME profile are the indications of improved properties of biodiesel, and therefore, indorses high fuel efficiency [60]. While other researchers using the same feedstock reported less number of FAMEs such as Takase et al [17] reported five FAMEs, Ullah et al, [59] reported seven FAMEs, and Fadhil et al [18] reported six FAMEs.…”
Section: Qualitative and Quantitative Analysis Of Smbmentioning
confidence: 98%
“…Biodiesel is considered a renewable transportation fuel due to its excellent properties such as biodegradability, nontoxicity, and bio-renewability. Biodiesel can be directly utilized in a compression ignition engine without modification [ 96 , 97 ]. Biodiesel production using a chemical catalyst is an energy-intensive process and also generates wastewater.…”
Section: Polymeric Matrices Immobilized Enzymes For Industrial Bio-ca...mentioning
confidence: 99%